PENGARUH PEMBERIAN PUPUK ORGANIK TERHADAP SIFAT FISIKA TANAH DAN HASILTANAMAN TOMAT (Lycopersicum esculentum Mill.)DI DESA BULUPOUNTU KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Uswah Hasanah, Danang Widjajanto, Fira Fermila Lawenga (AGROTEKBIS, 2015)
This researchaimed to determinethe effect of cow manureaddition to soil physicalpropertiessoil and tomatoplant yield. The research was conducted during September toDecember 2014in BulupountuVillage, Sigi Biromaru Sub District, Sigi Regency, Central Sulawesi Province.This research used a Randomized Block Design (RBD) with cow manurerates as the experimental treatments. The rates included without fertilizer (control), 15Mg ha-1, 30Mg ha-1 and45 Mg ha-1.Eachtreatment was replicated3timesso thatthere were 12experimental plots.Rising the cow manure rate significanltly increased plant height. Similar results also indicated by the number of tomato fruits except at 45 Mg ha-1the fruit number decreased. Applying 30 Mg ha-1 resulted in highest number of tomato fruit. The addition of cow manure significantly improvedsoilphysical properties. Soil bulk density, porosity and permeability declined significantly to only 1,56 g cm-3, 35.45 % and 2,18 cm jam-1 when the rate of cow manure increased to 45 Mg ha-1.